(untitled) (Global Journal of Human-Social Science, 2025)
This article investigates the developmental process of a child with autism during a writing task A fragment of pedagogical practice is presented from a historical-cultural perspective which emphasizes the centrality of language and the role of the other s word as a mediator of development Within this dialogical framework language functions as a space for recognition and participation moving the child from a state of isolation as suggested by autism s diagnostic criteria to one of social interaction The study discusses work with an eight-year-old boy named Miguel during the early years of elementary school His task of retelling a fable provided a concrete context for analyzing literacy as a form of immersion into the cultural world Such retelling tasks common in pedagogical practice aim to develop skills in text rewriting and written organization Miguel s engagement illustrates the developmental process of language-based social interaction Final considerations guided by Vygotskian theory and concept of singularity suggest that studying the constitutive singularities of an autistic child through writing activity reveals how multiple determinations shape the human experience Thus to dialogue with an autistic child is above all to dialogue with a human being and the unique singularities that constitute every person